Rahmatan Lil'alamin's Leadership in Islamic Education - Naufalia, Dwita Nisa Shafa; Suharyat, Yayat (MultiTech Publisher, 2023)
The Islamic concept of rahmatan lil alamin is presented and connected with various challenges and opportunities, as well as the weaknesses and strengths of the Indonesian nation, and also the objective conditions of Islamic education that still require revitalization, then the Islamic education model needed to face the nation's challenges is an education model based on rahmatan lil alamin. . With the application of the nine Islamic values rahmatan lil'alamin school is expected to be able to teach about the beauty of Islam in upholding peace. This research is a qualitative descriptive type with libraby research method, namely the elaboration of variable concepts of rahmatan lil'alamin in Islamic education from the Quran, hadiths, books and journals of Islamic scientists. The results showed that the strategy used by PAI teachers in instilling the nine Islamic values of rahmatan Iil'alamin was carried out in several ways, namely providing Islamic insights, through uswatun hasanah, as well as through case studies in the implementation of discussions. The result of the cultivation of the nine Islamic values of rahmatan Iil'alamin is the creation of a peaceful school atmosphere.